(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Alzheimer’s disease (AD) is associated with pathophysiological and psychological disturbances including cognitive decline, depression, anxiety and motor imbalance. Conventional drugs for managing AD do not address associated non-neurocognitive co-morbidities, hence the need to investigate alternative therapies especially from plants. The neuroprotective benefits of bromelain have been identified, but its impacts on scopolamine-induced neurotoxicity is yet to be elucidated. Twenty-Five male rats were separated randomly into 5 groups: Control (normal saline; 1ml/kg); Scopolamine (i.p; 1mg/kg); Bromelain (50mg/kg); Scopolamine + Bromelain; Scopolamine + Donepezil (reference drug, 1mg/kg). Neurobehavioral paradigms (novel object recognition, elevated plus maze, forced swimming and open field tests were assessed, followed by biochemical (MDA, SOD, AChE, NO, Total protein & IL-1b) assay in the PFC. Data were analyzed using one-way ANOVA (Tukey’s posthoc.). Values with p<0.05 were considered significant. Scopolamine reduced memory index (P<0.01) (cognitive function), ambulatory & rearing activities (P<0.05) (motor behavior), open arm duration (P<0.001) (anxiety-like behavior) & increased immobility time (P<0.05) (depressive-like behavior). Exposure to scopolamine also led to significant reduction in the prefrontal cortical levels of SOD (P<0.05) while increasing MDA (P<0.05), acetylcholinesterase (P<0.01) and IL-1β (P<0.05). However, levels of NO and total protein were not significantly altered. In contrast, intervention with bromelain or donepezil significantly reversed most of the behavioral and biochemical alterations induced by scopolamine. Bromelain compared favorably with donepezil in improving memory decline and other non-cognitive dysfunctions associated with scopolamine exposure. This could have resulted from modulation of oxidative stress, inflammation and cholinergic transmission. Key words: Bromelain; Scopolamine; Oxidative stress; Neurotoxicity; Neuro-inflammation; Behavior